(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background: Surgical sphincterotomy (SS) has been the most commonly used treatment for chronic anal fissure (CAF). Although effective, it is associated with gas and or fecal incontinence in (0-20%) inter-sphincteric Botulinum Toxin A (BTXA) injection is a non-surgical technique that may be used as an option under certain circumstances for treatment of such condition. Objective: To verify the effectiveness of the BTXA injection in relieving symptoms and healing of chronic anal fissures. Methods: Thirty patients with CAF were treated by BTXA 1 U/kg injected into the inter-sphincteric plane; as an outpatient procedure, patients were re-evaluated after 1 week, and then every 2 weeks until the fissure healed or surgery was required. The patients were followed up for one year by regular attachment through phone call or visit, to evaluate the effects of treatment. Results, complications and follow up were recorded. Results: In 25 patients (83%), the pain was disappeared after the first week; 20 patients (66%) presented with a complete healing of the fissure in a period ranging between 1 to 3 months. Gas incontinence was reported in 2 patients (6%) and solved spontaneously. No major complications were found, in 3 cases (10%) surgery was needed later on. Conclusion: Since it avoids the greater risk of incontinence associated with SS, and it can be done as outpatient procedure without admission or general anesthesia. We recommend the use of BTXA as the first therapeutic approach for patients with chronic anal fissure. Keywords: Botulinum Toxin A, anal fissure. Citation: Nashwan Q. Mahgoob, Muhammed M. kamal. Inter sphincteric botulinum toxin A injection for the management of chronic anal fissure. Iraqi JMS. 2017; Vol. 15(2): 181-187. doi: 10.22578/IJMS.15.2.11